Regiospecific N-alkyl substitution tunes the molecular packing of high-performance non-fullerene acceptors. Issue 1 (20th October 2021) - Qi, Feng; Jones, Leighton O.; Jiang, Kui; Jang, Sei-Hum; Kaminsky, Werner; Oh, Jiyeon; Zhang, Hongna; Cai, Zongwei; Yang, Changduk; Kohlstedt, Kevin L.; Schatz, George C.; Lin, Francis R.; et al.
Abstract : Single-crystals of a series of Bz-based NFAs derivatized via regiospecific N -alkyl engineering have been systematically studied. The J -aggregate-like packing in EHN6SEH-4F facilitates formation of ordered 3D channels for efficient charge transport. Abstract : The rapid development of non-fullerene acceptors (NFAs) with strong near-infrared absorption has led to remarkably enhanced short-circuit current density ( J sc ) values in organic solar cells (OSCs). NFAs based on the benzotriazole (Bz) fused-ring π-core have great potential in delivering both high J sc and decent open-circuit voltage values due to their strong intramolecular charge transfer with reasonably low energy loss. In this work, we have designed and synthesized a series of Bz-based NFAs, PN6SBO-4F, AN6SBO-4F and EHN6SEH-4F, via regiospecific N -alkyl engineering based on the high-performance NFA mBzS-4F that was reported previously. The molecular packing of mBzS-4F, AN6SBO-4F, and EHN6SEH-4F single crystals was analyzed using X-ray crystallography in order to provide a comprehensive understanding of the correlation between the molecular structure, the charge-transporting properties, and the solar cell performance. Compared with the typical honeycomb single-crystal structure of Y6 derivatives, these NFAs exhibit distinctly different molecular packing patterns. The strong interactions of terminal indanone groups in mBzS-4F and the J -aggregate-like packing in EHN6SEH-4F lead to the formation of ordered 3D networks in single-crystals with channels for efficient charge transport. Consequently, OSCs based on mBzS-4F and EHN6SEH-4F show efficient photon-to-current conversions, achieving the highest power conversion efficiency of 17.48% with a J sc of 28.83 mA cm −2 .